(untitled) (Singaporean Journal of Business Economics and Management, 2018)
Buffers are integral components of any production system that fits the type of system, its size can vary. Buffers marked changes in parameters such as time and cost of a system’s output. Given that the components of each system can be successful in his career. This study defined a problem and it will create a simulation model of a Job-shop system to using the Taguchi method, optimum size of the buffer (Optimal buffer allocation), and to assign them. The purpose of this type of allocation, reducing the total production time and thus to minimize the total cost of production. In this Job-shop system, each workshop includes a number of production machines. In problem-solving research related to the rate of arrival of parts to machines in the workplace and machine downtime random so we solve the problem in random conditions. The results of this experiment were checked. We can evaluate and use the results of this and similar problems compared with traditional measures, we know much more successful.